(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article presents a discussion of architecture for contemporary theater spaces. The following were established: to characterize and discuss contemporary practices of the scenic arts, identifying their spatial needs; and present guidelines for the construction of contemporary theaters. The methodology used was the bibliographical discussion, the examination of architectural examples and the study of the theatrical context. As conclusions it was possible to realize that cities have demands of new theaters and that these spaces should be flexible environments and that favor a closer and interactive relationship between the public and actors, favoring modern scenography, sound, projection and lighting technologies.